COVID-19 vaccination: challenges in the pediatric population - Azoicai, Alice Nicoleta; Miron, Ingrith; Lupu, Ancuta; Alexoae, Monica Mihaela; Starcea, Iuliana Magdalena; Alecsa, Mirabela; Lupu, Vasile Valeriu; Danielescu, Ciprian; Nedelcu, Alin Horatiu; Salaru, Delia Lidia; Dragan, Felicia; Ioniuc, Ileana (Frontiers in Public Health, 2025)
Vaccination is considered to be one of the most effective means of protecting individuals and populations from the risks associated with exposure to various pathogens. The COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), affected people of all ages worldwide. In response, several pharmaceutical companies rapidly leveraged their resources to develop vaccines within a very short period of time, leading to the introduction of new, improved, and combination vaccines for community-wide immunization. This review aims to provide a summary of the available literature on the efficacy and safety of COVID-19 vaccines in the pediatric population ranging from 0 to 18 years. An analysis of recent published studies reveals that the majority of clinical trials have reported a sustained immune response following COVID-19 vaccination in children across various age groups worldwide. The majority of the authors highlighted the effectiveness and safety of immunization schedules in children and adolescents. The population-level efficacy of this vaccination remains to be determined, provided that the benefits outweigh the potential risks. Long-term side effects must still be monitored to enable the development of safer and more effective vaccines for future pandemics.